2017
DOI: 10.1007/s00773-017-0457-7
|View full text |Cite
|
Sign up to set email alerts
|

On the strong scalability of maritime CFD

Abstract: Since 2004, supercomputer growth has been constrained by energy efficiency rather than raw hardware speeds. To maintain exponential growth of overall computing power, a massive growth in parallelization is under way. To keep up with these changes, computational fluid dynamics (CFD) must improve its strong scalability-its ability to handle lower cells-per-core ratios and achieve finer-grain parallelization. A maritime-focused, unstructured, finite-volume code (ReFRESCO) is used to investigate the scalability pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Thus, the computational time is expected to be several times that achieved with the standard kω model. That is, albeit the solution of turbulence equations scales better than momentum equations (Hawkes et al, 2018). Although the RST model boasts of modelling turbulent physics more robustly than two-equation models, there are problems in its practical implementation (Parneix et al, 1998).…”
Section: Physics Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the computational time is expected to be several times that achieved with the standard kω model. That is, albeit the solution of turbulence equations scales better than momentum equations (Hawkes et al, 2018). Although the RST model boasts of modelling turbulent physics more robustly than two-equation models, there are problems in its practical implementation (Parneix et al, 1998).…”
Section: Physics Modellingmentioning
confidence: 99%
“…Although their focus was predominantly on aerospace applications, several aspects overlap significantly with the field of computational ship hydrodynamics. This prompted Hawkes et al (2018) to address one of the concerns raised by Slotnick et al (2014), specifically, scalability problems of CFD simulations with increasing cell numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these lax convergence tolerances, previous work [7] and other literature [8,9] has shown that repeatedly finding a solution to the linearized pressure equation is a severe bottleneck to the strong scalability of CFD codes. The pressure equation is a stiff, elliptic, Poisson equation which contains many low-frequency error components [10].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these methods require global communication patterns which scale very poorly. Efforts to hide or reduce the number of global communications, such as the 'pipelined' version of GMRES (P-GMRES [11]), or improved bi-conjugate gradient methods (IBCGS [12]), provide only minor improvements for parallel CFD [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation